Microlearning-Based Video Tutorials to Enhance Basic Counseling Skills of Guidance and Counseling Students - Djauhari, Usman; Rahim, Maryam; Bouty, Abd Aziz (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to: (1) develop microlearning-based video tutorials for learning basic counseling skills that are valid and contextual, and (2) determine the level of validity, practicality, and effectiveness of the microlearning-based video tutorials in improving basic counseling skills. This study employed a Research and Development method using the Dick and Carey development model, which consists of ten stages. The research subjects included two expert validators (content expert and media expert), ten students in the small-group trial, and twenty fifth-semester students of the Guidance and Counseling Study Program in the large-group trial. The research instruments consisted of expert validation sheets, practicality questionnaires, and pretest and posttest instruments on basic counseling skills. Data were analyzed using descriptive statistics with Likert scale conversion and N-Gain Score analysis to measure product effectiveness. The results of the study indicate that: (1) the developed microlearning-based video tutorials cover seven basic counseling skills, namely reflection, exploration, paraphrasing, interpretation, confrontation, focusing, and clarification; (2) the product validity is categorized as highly feasible, with average scores of 4.55 from the content expert and 4.45 from the media expert; the practicality level is categorized as very practical, with average scores of 4.27 in the small-group trial and 4.26 in the large-group trial; and (3) the microlearning-based video tutorials are proven effective in improving students’ basic counseling skills, as indicated by an increase in the average score from 47.9 in the pretest to 95.5 in the posttest, an N-Gain score of 0.66 (moderate category), and an effectiveness level of 79.6% (effective category). The developed product can be utilized as a supporting medium for counseling practicum learning as well as an independent learning resource for university students.